Photodynamic therapy for malignant brain tumors in children and young adolescents - Chiba, Kentaro; Aihara, Yasuo; Oda, Yuichi; Fukui, Atsushi; Tsuzuki, Shunsuke; Saito, Taiichi; Nitta, Masayuki; Muragaki, Yoshihiro; Kawamata, Takakazu (Frontiers in Oncology, 2022)
Photodynamic therapy (PDT) targets tumor cell remnants after resection. Here, we evaluated the feasibility of PDT for malignant brain tumors in children and young adolescents. This was a single-center, non-randomized, phase I/II clinical study. The primary endpoints were the safety of treatment with talaporfin sodium (TS) (phase I) and overall survival (OS) after PDT (phase II). The secondary endpoint was progression-free survival (PFS) after PDT. The TS dose was determined by dose escalation from 10 to 20 to 40 mg/m2 for every three cases starting from the initial enrolled case. Eight patients with a mean age of 170.2 months (129–214 months) at the time of PDT received nine procedures with a mean follow-up duration of 16.8 months (1–42 months) after PDT. Histopathological diagnoses included supratentorial anaplastic ependymoma (n=2), anaplastic astrocytoma (n=1), diffuse midline glioma with H3K27M mutation (n=1), glioblastoma (n=3), and pediatric-high grade glioma (n=1). The outcome was survival in five patients and death in three patients. Recurrence occurred in six of the eight patients; the remaining two were recurrence-free after PDT. Therefore, OS and PFS were calculated as 21 and 6 months, respectively. Seizures and fevers, which were likely surgery-related symptoms, were commonly observed. Photosensitive skin rashes or liver dysfunction, which are common adverse effects in adults, were not observed. Our results showed that TS can be used safely in children at doses comparable to those used in adults, as there was no major complication associated with TS administration. However, we cannot make a definitive conclusion about the efficacy of PDT because of the small number of participants. Accumulating cases was difficult because of the rarity of pediatric brain tumors and the difficulty in making a preoperative differential diagnosis, considering the wide range of histopathological findings. Besides, the psychological stress associated with light-shielding management in pediatric patients was more severe than initially expected. In conclusion, TS at doses comparable to those used in adults may be safe for use in children and young adolescents between the ages of 6 and 20 years. However, further studies are needed to clarify its efficacy.